Rubin's pathology clinicopathologic foundations of medicine - Rubin, Raphael; Strayer, David S. (Lippincott Williams & Wilkins, 2012)
Provides medical students with a lucid discussion of basic disease processes and their effects on cells, organs, and people. This title features streamlined coverage that includes only what medical students need to know and provides clinical application of the chapter concepts.